PENGARUH EDIBLE COATING TERHADAP KAPASITAS AIR TERIKAT SEKUNDER DAN TERSIER MANISAN TOMAT CHERRY SELAMA PENYIMPANAN - Priska Wisudawaty, indah Yuliasih, dan Liesbetini Haditjaroko (Jurnal Teknologi Industri Pertanian, 2016)
The use of an antimicrobial edible coating is a technique that can be developed and applied to keep thequality and extend the shelf life of products, such as candied cherry tomato. This study purposed to getprocessing technology candied cherry tomatoes, to formulate edible coating with cinnamon oil as anantimicrobial, and to analyse the effect of edible coating to changes in the quality of candied cherry tomatoesduring the storage process. The stages of this research were the production process of candied cherry tomatoes,which consisted of determining treatment cherry tomatoesas a whole and sliced cross, a combination of sugarconcentration and immersion time in a sugar solution, and determination of drying time candied cherrytomatoes. The next steps were manufacturing and characterization of antimicrobial edible coating, and thenapplication of antimicrobial edible coating during 12 weeks of storage. Based on the results, the best treatmentprocessing of candied cherry tomatoes was a cherry tomato with an intact form and had 40-55-70% gradedsugar concentration during 12 hours immersion time, and at 33 hours drying time. Moreover, resultedfromedible coating formula was tapioca starch, CMC, glycerol, stearic acid and cinnamon oil with percentagesof 3.0%, 0.4%, 5.0%, 0.5%, and 0.6%, respectively. During storage, lowest secondary and tertiary bound watercapacity on candied cherry tomatoes with an antimicrobial edible coating that was Ms of 25.32%, awsof 0.58 andMt of 42.11%. Likewise, the lowest rate of microbial growth was from candied cherry tomatoes with anantimicrobial edible coating.Keywords: antimicrobial, bound water capacity, candied cherry tomato, cinnamon oil, edible coating